Besoins de recherche en santé au travail pour les salariés d’entreprises de sous-traitance interne - Michel Hery (Perspectives Interdisciplinaires sur le Travail et la Santé)
Industrial subcontracting, and particularly the use of contractors for maintenance operations in process industries, has developed significantly in France over the last thirty years. Several studies of the subject have shown that contracting firm employees are more frequent victims of occupational accidents than their colleagues working for the companies in control of the premises. A strict comparison has, however, always been impossible, since the contractors’ employees perform tasks that are different from those of the permanent workers. Moreover, in several activities (industrial furnace bricklayers, maintenance operations in the chemical industry) it has been clearly shown that exposure limit values are often exceeded. The author suggests that, as is the case in the nuclear industry, joint studies involving researchers from different specialty areas should be performed to obtain a better understanding of the phenomena (relationship between principal and contractors, particular forms of work organization, etc.) underlying the higher number of occupational accidents and high exposure levels.